FOOT AND MOUTH DISEASE CONTROL STRATEGIES GLOBALFRAME WORK: Life Sciences-Virology - SINGH, S.N. (International Journal of Life Science and Pharma Research, 2011)
Livestock sector revolution is the global phenomenon under the critical gap of Food Nutritional security to the world. Asia and the Indian dairy farming and agriculture business has grown to Himalayan heights to put the country as number one milk producer in the world today with above 106 million tons record production. The country has a huge livestock population (500million livestock) of cattle, buffaloes, sheep and goats. A small ruminant are in desert and hilly track of Indian subcontinent e.g HP, J & K, Rajasthan, Tamilnadu are the major habitant for rural economy mainly for marginal and landless community. Piggery population in NE states, Vietnam, phillipines EU and North America have significant contribution in food security even for poor people of the particular nation as a live hood programme. The production of livestock products like milk, meat, wool, hides and other byproducts have also increased tremendously in recent years. This sector has been recognized world wide as an economic agenda globally.